Triple Trouble: Disseminated Penicilliosis in a Cancer patient with COVID-19 - Kamtalwar, Sujeet; Mirgh, Sumeet; More, Ashwini; Gokarn, Anant; Dhumal, Sachin; Sharma, Palak; Lall, Sujata; Patkar, Nikhil; Shetty, Nitin; Chatterjee, Gaurav; Rajpal, Sweta; Bhat, Vivek; Khattry, Navin; Gupta, Sudeep (Indian Journal of Medical and Paediatric Oncology, 2023)
Penicilliosis is a fungal infection caused by the fungus Penicillium marneffei or Talaromyces marneffei. Penicillosis is commonly seen in immunocompromised patients such as in HIV(AIDS). Herein, we present a case of penicilliosis in an oral cavity cancer patient who was admitted for the management of SARS-CoV-2 infection at our hospital. A 50-year-old male patient operated on for squamous cell carcinoma of the oral cavity who completed his adjuvant chemoradiation 2 months ago, presented to our hospital with dry cough for more than 3 weeks. His nasopharyngeal swab was positive for the severe acute respiratory distress syndrome (SARS-CoV-2). During his hospital stay for SARS-CoV-2 infection, he was diagnosed with disseminated penicilliosis. The patient was treated with intravenous antifungals caspofungin and voriconazole. However, he succumbed to disseminated fungal sepsis. This case highlights the need to consider penicilliosis as a possible opportunistic pathogen, especially in immunocompromised patients such as cancer.
Keywords: penicilliosis; cancer; oral cavity; SARS-CoV-2; COVID-19